BEYOND PAYCHECKS: BUILDING A HUMAN-CENTRIC STRATEGY FOR THE MODERN WORKFORCE - Dian Molivia; Ramon Zamora; Dhenny Asmarazisa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The modern workforce is no longer solely motivated by financial compensation, as evidenced by high disengagement and turnover rates despite competitive pay. This article argues that a fundamental shift toward a human-centric organizational strategy is essential for sustainable success. The objective is to define the core pillars of this strategy and present a framework for implementation. The methodology involves a synthesis of contemporary workforce research, analysis of emerging organizational models, and a review of qualitative data on employee priorities. The results and discussion identify four foundational pillars: Purpose and Autonomy, Growth and Development, Holistic Well-being, and Connection and Recognition. The discussion contends that these elements form an integrated system that addresses the whole employee, thereby fostering resilience and performance. The conclusion posits that organizations investing in this human-centric model will achieve a superior return on investment through enhanced talent retention, innovation, and engagement, moving beyond transactional employment to build a sustainable competitive advantage.